Control de inventarios y su incidencia en la Rentabilidad en la empresa supermercados La Inmaculada SAC periodo 2014 - Arévalo Sánchez, Pamela (2014)
The present work has like main aim determine the incidence of the control of inventories in the Profitability of the company Supermercados la Inmaculada S.A.C - Period 2014, whose main economic activity is the sale by minor of varied products (useful of desk, products of first need, articles of Bazar, etc). It used the type of Basic investigation; since it looks far of general form the description of the behavior of the variables, that in the same refers to the control of inventories of commodities and his behavior inside the supermarkets, the design of the investigation is No Experimental, since it does not exist the Application of statistical formulas, since it is a study that realizes without the deliberate manipulation of the variables. The results obtained in the investigation attained through qualitative technicians and of work of field that have allowed to establish an analysis on the reality of the company. Likewise it managed to verify that in Supermercados la Inmaculada S.A.C, a good control of Inventories exists, sufficient and necessary merchandise to the disposition of the client; it is reflected in the financial statements. It has attained contrast and verify the hypothesis posed, concluding that the good control of inventories incide favorablemente in the profitability and improves the levels of existence of available commodity for the sale of the company Supermercados la Inmaculada S.A.C; it concluded also that the application of a suitable control of inventories helps to keep a considerable stock with a level of favourable rotation, contributing with this to the full satisfaction of the customers and allowing obtain greater profitability for the company.